Mid-Cenozoic fluvio-deltaic to marine environments of the Salin Sub-basin, Central Myanmar. (1st April 2020) - Gough, Amy; Hall, Robert; BouDagher-Fadel, Marcelle K.
Graphical abstract: Highlights: New outcrop investigations of the Salin Sub-basin build on previous core-scale interpretations. Shwezetaw, Padaung, and Okhmintaung Formations are fluvio-deltaic to shallow marine sediments. Record a high rate of sedimentation into the basin. Subsidence broadly kept pace with sediment supply during Oligocene and Miocene. Abstract: The Salin Sub-basin is one of several basins within the wide elongate north-south trending Central Basin in Myanmar. A field-based campaign targeted the deposits of the reportedly Oligocene Shwezetaw, Padaung, and Okhmintaung Formations, which previously have been described only from spatially-restricted and incomplete core records and limited field studies. A minimum of 2.5 km thickness of these formations in the sub-basin records a high sedimentation rate and long-term subsidence which broadly kept pace with sediment input. Facies analysis, based on sedimentary logs and panel diagram interpretation, interprets these formations as deposits of large-scale broadly southward-flowing fluvial systems that interacted with deltaic and shallow marine environments in the southwestern parts of the basin. A switch from south- to southwest-flowing rivers midway down the basin suggests these systems fed sediment to offshore basins in the west. The overall environment was somewhat similar to the modern-day Irrawaddy River and Delta. Despite the recorded high sedimentation rates, and the coeval subsidence, the depositional environment does not show much variation. The main control is overall relative sea-level rise, associated with a northeastward marine transgression into the basin with contemporaneous smaller-scale cycles of sea level rise and fall. In terms of basin development, this considerable thickness of clastic sediment indicates significant emergent sources. Palaeoenvironment reconstructions suggest that the south-flowing fluvial systems sourced sediment from the northern margin of the basin, but there were also some channels joining the main channel from the western margin of the basin and fewer channels from the northeast.